Navigating the Island of Reil: how to understand the insular cortex. Issue 2 (14th December 2016) - Wynford-Thomas, Ray; Powell, Rob
Abstract : Insular-onset seizures are rare and easily misdiagnosed. In this article, we aim to highlight the often distinctive semiology of seizures involving the insula with reference to three cases. We suggest three points to aid the recognition of seizures involving the insula: (1) Seizures originating in the insula frequently present with a sensation of laryngeal constriction, dyspnoea or unpleasant somatosensory symptoms; (2) Seizures involving the anterior insula may have a silent onset, but tend to propagate rapidly to motor areas causing motor or hypermotor symptoms; (3) Seizures involving the posterior insula cause somatosensory symptoms, which are normally contralateral to the seizure onset.